Matematikundervisningens sociopolitiska utmaningar - Valero, Paola; Björklund Boistrup, Lisa; Christiansen, Iben; Norén, Eva (Stockholm Studies in Mathematics and Science Education, 2022)
Today's mathematics education has an impact even outside the confines of the classroom, not least through the relevance of mathematics in culture, economics, politics and in relation to power. Sociopolitical perspectives in mathematics didactic research provide insights into how education in mathematics is social and political. Research based on these perspectives suggests both critical questioning and not-yet-imagined possibilities for content, teaching, policy and further research. This book introduces, for a larger Swedish audience, the research orientations and strategies that sociopolitical perspectives have to offer. In the book, this is illustrated in several ways. The chapters describe current research on the socio-political challenges of mathematics education in several different contexts, e.g. classrooms, after-school programs, curricula, mathematics teacher education and even mathematics education research. In this way, perspectives are broadened to groups of people, institutions and forces, which constitute a network of mathematics education practice. The chapters present different philosophical and empirical studies, based on theoretical tools from philosophy, social science and cultural studies, critical studies of education and socio-cultural-political studies of mathematics education. Methodological and analytical strategies such as text and discourse analysis and case studies of practice are used. In this way, opportunities to research mathematics education based on socio-political perspectives are illustrated. The chapters use various writing styles which invite the reader into the world of research. Thus, the reader will encounter different ways of thinking about the role of mathematics education in the creation of modern Swedish society.